2018
DOI: 10.1021/acsomega.7b01878
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals as Dynamic Surface Ligands To Control Nanoparticle–Protein Interactions

Abstract: The rapid formation of the protein corona on to the nanoparticle (NP) surface is the key that confers biological identity to NPs and subsequently dictates their fate both in vitro and in vivo. Despite significant efforts, the inability to control the spontaneous interaction of serum proteins with the administered NPs remains a major constraint in clinical translation of nanomedicines. The ligands present on the NP surface offer promise in controlling their biological interactions; however, their influence on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…When our group recently compared the interaction of gold nanoparticles of different morphologies (spheres, cubes, prisms, and rods) yet coated with the same surfactant (CTAB) with the human serum, we noted that the strength of serum–nanoparticle interactions is remarkably influenced by the particle morphology . Another study from our group on Ag nanoparticles of similar shape and size yet of different capping agents has revealed that the surface ligands also greatly influence the nanoparticle–serum interactions . Such independent observations, for instance, the influence of nanoparticle characteristics on their interactions with serum, and the effect of the presence of serum on nanoparticle cellular uptake and toxicity, emphasize on the importance of controllably varying single nanoparticle characteristic one-at-a-time to obtain a more detailed understanding of the nano–bio interactions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…When our group recently compared the interaction of gold nanoparticles of different morphologies (spheres, cubes, prisms, and rods) yet coated with the same surfactant (CTAB) with the human serum, we noted that the strength of serum–nanoparticle interactions is remarkably influenced by the particle morphology . Another study from our group on Ag nanoparticles of similar shape and size yet of different capping agents has revealed that the surface ligands also greatly influence the nanoparticle–serum interactions . Such independent observations, for instance, the influence of nanoparticle characteristics on their interactions with serum, and the effect of the presence of serum on nanoparticle cellular uptake and toxicity, emphasize on the importance of controllably varying single nanoparticle characteristic one-at-a-time to obtain a more detailed understanding of the nano–bio interactions.…”
Section: Introductionmentioning
confidence: 95%
“…The serum is rich in proteins and growth factors which make it effective in mimicking the protein-rich environment of the blood. When nanoparticles are exposed to an in vivo biological environment, the serum proteins tend to form a protein corona on the nanoparticle surface, which is believed to give nanoparticles a biological identity. , Therefore, it is important to understand the role of serum proteins in influencing the biological action of nanoparticles. In the current study, the importance of a protein corona in mediating cellular uptake and toxicity has been determined by performing toxicity and cellular uptake studies in three environments with different serum levels.…”
Section: Rationale For Determining the Effect Of Serum Proteinsmentioning
confidence: 99%
“…2830 Because there were several reports on protein-protected Au and Ag NCs and hence from the knowledge of biocompatibility, we have chosen Cu NCs for the present study. 3134 Steady-state and time-resolved fluorescence spectroscopy show that the Cu NCs bind to the various BSA pockets which results into different extents of PET with the MV derivatives. The fluorescence intensities and change in the excited-state lifetime of the Cu NCs provide a quantitative idea about the different domain-specific pockets in BSA.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the application of AgNPs after virus inoculation could increase the probability of a high number of nano-silver particles to target the viral proteins and/or the whole virus particle that eventually exhibit outstanding e ciency in suppressing BYMV disease compared to preventive applications of AgNPs applied at the same concentrations. The AgNPs-plant protein interactions are not documented clearly but other previous studies stated that the initial interaction between proteins and metal nanoparticles changes their in vivo properties and has remarkably altered the mechanism of nanoparticle interaction with other cell targets (41).…”
Section: Discussionmentioning
confidence: 99%